2014
DOI: 10.1186/1471-2458-14-644
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sri Lankan cause-specific adult mortality 1950–2006

Abstract: BackgroundAlthough all-cause mortality in Sri Lanka decreased significantly from 1950 to 1970, subsequent declines have been more modest with divergent trends by age and sex. This study investigates these trends through cause of death analysis for 1950–2006 in adults aged 15–64 years.MethodsDeaths were obtained from the World Health Organisation (WHO) mortality database for 1950 to 2003, and the Department of Census and Statistics Sri Lanka for 1992–95 and 2004–06 where WHO data was unavailable. Adult deaths w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…According to the WHO 2014 update, the three highest causes of death in Sri Lanka were reported as CVD, stroke, and diabetes. A study done on trends in Sri Lankan cause-specific adult mortality concluded that chronic diseases are the greatest cause of morbidity and mortality and highlighted the importance in adaptation of the health sector to this alarming trend [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO 2014 update, the three highest causes of death in Sri Lanka were reported as CVD, stroke, and diabetes. A study done on trends in Sri Lankan cause-specific adult mortality concluded that chronic diseases are the greatest cause of morbidity and mortality and highlighted the importance in adaptation of the health sector to this alarming trend [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1950, Sri Lanka has experienced an impressive decline in all-cause mortality in adults aged 35 to 64 years from reductions in infectious disease in women, and little change in noncommunicable disease (NCD) mortality rates, with a consequent increase in proportional mortality from CVD and cancer to 53% by 2002-2006. 1 By contrast, in men, there was little decline in the mortality rate for over half a century, with CVD and cancer mortality replacing infection as the main cause of death, and accounting for 40% of proportional mortality by 2002-2006, similar to women, but at much higher mortality rates. The latest Sri Lanka mortality data for 2011-2013, after the end of the civil war in 2009, indicate a life expectancy of 72 years for men and 79 years for women.…”
Section: Introductionmentioning
confidence: 99%
“…During the past century Sri Lanka has experienced declines in rates of infectious disease mortality in women, leading to reduction in total female mortality and continued improvement in female life expectancy. By contrast, the absolute decline in infectious disease mortality in men has been accompanied by increased cardiovascular disease (CVD) mortality, leading to a prolonged plateau in male life expectancy [1]. The increasing burden of non-measures, with less emphasis on the high-risk approach and more stress on a population approach [3,4].…”
Section: Introductionmentioning
confidence: 99%